Battery energy storage system (BESS) design for peak demand reduction, energy arbitrage and grid ancillary services - Abdullah W.S.W.; Osman M.; Kadir M.Z.A.A.; Verayiah R. (Institute of Advanced Engineering and Science, 2023)
Renewable Energy (RE) penetration is a new phenomenon in power systems. In the advent of high penetration of RE in the systems, several issues have to be addressed especially when it involves the stability and flexibility of the power systems. Battery Energy Storage System (BESS) has gained popularity due to its capability to store energy and to serve multiple purposes in solving various power system concerns. Additionally, several BESS can be combined to operate as Virtual Power Plant (VPP). This study will involve the design and implementation of BESS for five potential customer sites for the demonstration project and to be possibly integrated into one VPP system. The study is expected to demonstrate bill savings to the customers with BESS due to peak demand reduction and energy arbitrage savings. 2020, Institute of Advanced Engineering and Science. All rights reserved.